Pengembangan dan Penerapan Alat Pemotong Bakso di UMKM Keluarahan Tamansari Guna Mengurangi Risiko Kecelakaan Kerja - Asih Setyo Rini; Irfan Muhammad; Siti Hanan; Febry Aurora Galla; Mochamad Farel Akbar; Sulis Setya Damayanti; Sinta Purnamasari; Winda Safitri; Hida Nurhekmy; Ajeng D.P Indrageni; Marini Marini; Yuliyanti Yuliyanti; Muhammad Ari Yanuar; Hadi Nur Amanah; Muhammad Faiz M.S; Asep Eka Mulyadin (Jurnal Kabar Masyarakat, 2023)
The cutting tools used today are very traditional using a blade without a base. The Appropriate Technology recommended to the public is in the form of a meatball cutting tool to reduce work accidents such as cut hands. The purpose of carrying out this activity is to apply cutting tools using the right technology and increase knowledge about anticipating accidents while working. The methods used with partners are observation, interviews and outreach. Based on the results of interviews and joint discussions with UMKM actors, they really need cutting tools that can speed up the production process and provide safety to UMKM partners for workers. The conclusion from the effort to implement this meatball cutting tool is still the 75% expected by UMKM partners because the standard meatball size tool is too thin and for safety in terms of cutting tools this gets a percentage of 100% because with this tool there is little chance of a small cut.